Phase 1b clinical trial of pucotenlimab (HX008), a novel anti-PD-1 monoclonal antibody, combined with gemcitabine and cisplatin in the first-line treatment of metastatic triple-negative breast cancer - Cao, Jun; Wang, Biyun; Zhang, Jian; Tao, Zhonghua; Wang, Leiping; Hu, Xichun (Frontiers in Oncology, 2022)
Background: Pucotenlimab, also called HX008, is a humanized anti-PD-1 antagonist IgG4 mAb，that blocks the interaction between human cell surface receptor programmed death-1 (PD-1) and its ligands, programmed death ligand 1 and programmed death ligand-2. Gemcitabine plus cisplatin (GP) has shown impressive antitumor activity as first-line therapy for metastatic triple- negative breast cancer (mTNBC) in CBCSG 006 trial. The phase 1b study was conducted to assess the safety and preliminary antitumor activity of pucotenlimab, combined with GP in patients with mTNBC in the first-line setting. Methods: Eligible patients were mTNBC with ≥6 months DFI (disease-free interval) who never received antitumor therapy for metastatic disease. Participants received pucotenlimab at 3mg/kg (d1, q3w) plus gemcitabine at 1250mg/m2 (d1, 8, q3w) and cisplatin 75mg/m2 (d1, q3w). Eligible patients received up to 6 cycles of pucotenlimab in combination with GP chemotherapy, while pucotenlimab could be maintained until disease progression or unacceptable toxicity occurred or withdrawl of informed consent. This study was registered in China, register number was CTR20191353. Results: Between July 2019 and March 2020, a total of 31 patients were enrolled in this study. Median age was 50 (range 28-68) years. Among 31 patients who were evaluated, 25 (80.6%) experienced objective response and the other 6 (19.4%) experienced stable disease (SD). As of August 4, the median progression free survival (PFS) was 9.0 months (95%CI，6.2-9.2). The most common grade 3 or 4 treatment-related adverse events included neutropenia (74.1%), anemia (35.5%), thrombocytopenia (32.3%), hypocalcemia (9.7%), hypokalemia (9.7%), and alanine aminotransferase increased (6.5%). There were no treatment-related deaths. Conclusion: Pucotenlimab plus GP demonstrated promising activity and manageable safety profile in patients with mTNBC in the first-line setting.